2011
DOI: 10.1097/jnn.0b013e31820c94da
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of the Relatives of Patients Undergoing Cranial Surgery for a Brain Tumor

Abstract: The functional changes that develop because of neurological sequelae in patients with a brain tumor have a negative effect on daily activities and self-care. This situation in turn has a negative effect on the lives of the patients' relatives and increases their work load. We interviewed 10 relatives of patients who had undergone cranial surgery for a brain tumor as part of a descriptive qualitative study and asked them to describe their experiences during the perioperative period and home care. The data obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…"A surgery was conducted without any elucidation and upon obtaining a sign on a paper. Further, there was lack of support as to whom was to be approached" (Tastan 2011).…”
Section: Category 2: the Varying Information Needs Of Caregiversmentioning
confidence: 99%
“…"A surgery was conducted without any elucidation and upon obtaining a sign on a paper. Further, there was lack of support as to whom was to be approached" (Tastan 2011).…”
Section: Category 2: the Varying Information Needs Of Caregiversmentioning
confidence: 99%
“…The 20 studies that were included comprised 342 participants (207 women, 81 men and 54 not classified). The focus was on the following themes: the needs of the next of kin2 20–24; their overall experiences as next of kin10 25–27; coping and coping strategies28–30; postoperative caregiving31 32; being a next of kin in the palliative phase33 34; experienced support factors35; how the caregiving changed over time36 and factors influencing treatment choice in the palliative phase 37. Three of the studies were undertaken 6 months after diagnosis,27 30 31 36 and three in the patients’ palliative phase or postmortem 33 34 37.…”
Section: Resultsmentioning
confidence: 99%
“…This support included emotional support and assistance during patient care and treatment. 2 10 20-27 [29][30][31][32][33][34][35] Open access…”
Section: Metasummariesmentioning
confidence: 99%
“…34 Although we chose to limit our search for BPC to glioma patients, our findings are similar to those reported from studies including all types of primary brain tumor patients (glioma, brain metastases, meningioma and other benign tumors). In 2 small studies, 13% to 16% of brain tumor patients had behavioral problems, 10,40 while in a large study, 34% of the patients experienced behavioral changes. 39 Moreover, 2 other studies of patients with various primary brain tumors found that 56% of caregivers had problems coping with the changes in patients' behavior, 14 and also that personality changes exacerbated stress of caregivers.…”
Section: Discussionmentioning
confidence: 98%